A four-year surveillance program for detection of Plasmodium falciparum chloroquine resistance in Honduras - Gustavo A Fontecha; Ana L Sanchez; Meisy Mendoza; Engels Banegas; Rosa E Mejía-Torres (Memorias do Instituto Oswaldo Cruz, 2014)
Countries could use the monitoring of drug resistance in malaria parasites as an effective early warning system to develop the timely response mechanisms that are required to avert the further spread of malaria. Drug resistance surveillance is essential in areas where no drug resistance has been reported, especially if neighbouring countries have previously reported resistance. Here, we present the results of a four-year surveillance program based on the sequencing of the pfcrt gene of Plasmodium falciparum populations from endemic areas of Honduras. All isolates were susceptible to chloroquine, as revealed by the pfcrt “CVMNK” genotype in codons 72-76.